The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1970
DOI: 10.1063/1.1653422
|View full text |Cite
|
Sign up to set email alerts
|

Outdiffusion Through Silicon Oxide and Silicon Nitride Layers on Gallium Arsenide

Abstract: Backscattering of MeV 4He ions has been used to analyze the Ga and As content in SiO2 and Si3N4 dielectric layers deposited on single-crystal GaAs substrates. Changes in impurity concentrations and distributions are seen after isothermal annealing at both 750 and 800°C. Evidence for Ga outdiffusion is clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1975
1975
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(26 citation statements)
references
References 6 publications
0
25
0
1
Order By: Relevance
“…Hence, traces of GaO oxide could be located out of the interface and are presumably formed through Ga outdiffused into silicon oxide, as the SiO 2 ap- pears to be a weak diffusion barrier for Ga. 35 Concerning the reported c-Ga 2 O 3 /GaAs structure which displays a very low interface state density, 2,3 we remark that such a structure in the samples with the lowest interface state density ͑i.e., G and F͒ is unlikely here; on the one hand, we have found that detected oxidized gallium prevails in its lower oxidation state, and, on the other hand, the increase of the unpinning index is also related to the onset of ͓Ga-Si͔. As shown above, the Ga-O bonds are strongly related with the gap states.…”
Section: B Interrelations Of Chemical and Electronic Structures Of Tmentioning
confidence: 79%
“…Hence, traces of GaO oxide could be located out of the interface and are presumably formed through Ga outdiffused into silicon oxide, as the SiO 2 ap- pears to be a weak diffusion barrier for Ga. 35 Concerning the reported c-Ga 2 O 3 /GaAs structure which displays a very low interface state density, 2,3 we remark that such a structure in the samples with the lowest interface state density ͑i.e., G and F͒ is unlikely here; on the one hand, we have found that detected oxidized gallium prevails in its lower oxidation state, and, on the other hand, the increase of the unpinning index is also related to the onset of ͓Ga-Si͔. As shown above, the Ga-O bonds are strongly related with the gap states.…”
Section: B Interrelations Of Chemical and Electronic Structures Of Tmentioning
confidence: 79%
“…[9][10][11] For example, these dielectrics are used for surface protection, electrical insulation in laser diodes, antireflection coatings, and distributed Bragg reflectors, and for selective quantum well (QW) intermixing. The previous studies of SiO 2 /and SiN x /GaAs junctions have revealed Ga diffusion into the insulators, [12][13][14] As diffusion into the insulators, 13 As-cluster formation due to nitridation and annealing of GaAs, 15 annealing-induced improvement of the interfaces, 15,16 and defect formation at high-temperature annealings. 17 Recently, it was also reported that pre-treatment of SiO 2 /GaAs interface has an effect on GaInAsN QW photoluminescence (PL) and Ga 3d photoemission, 8 exemplifying the significance of the interface engineering.…”
mentioning
confidence: 98%
“…To decide whether this is an influence of the surface of the substrate (OKAMOTO, SAKATA) or the effect of out-diffusion (TUCK et al 1979;GYULAI et al) heat treatment experiments were done. It was supposed that the "out-" and the ''in-" diffusion have the same probability (TUCK 1988).…”
Section: Resultsmentioning
confidence: 99%